Recent Advances in Chemical Mechanical Polishing Technologies of Silicon Carbide - Zeng, Qunfeng; Sun, Shichuan (Fine Chemical Engineering, 2023)
Silicon Carbide (SiC) as the third generation semiconductor material has a very high surface quality requirement, which is the core index in the engineering application. Chemical Mechanical Polishing (CMP) is the only technology that can realize global flattening and non-damage surfaces at present. In this paper the recent advances in traditional CMP, the effects of slurry, and hybrid CMP of SiC were reviewed. The principles and recent developments of CMP were introduced. Then the influence of various factors of slurry on polishing performance was discussed. In addition, recent advances in hybrid CMP technologies, such as Electrochemical Mechanical Polishing (ECMP), Photocatalytic Chemical Mechanical Polishing (PCMP), Plasma Assisted Polishing (PAP), Catalyst-Referred Etching (CARE) were reported, especially some efforts to make these technologies environmentally friendly. Finally, some shortcomings of CMP technology in the application of SiC are summarized and prospect its future development trends.